Macro Scheduler code for data collection - Inkpen,M; Lemmer,M; Fitzpatrick,N; Costa-Milan,D; Nichols,RJ; Long,NJ; Albrecht,T (2015)
Supporting information associated with the publication "New insights into single-molecule junctions using a robust, unsupervised approach to data collection and analysis", J. Am. Chem. Soc., 2015, DOI: 10.1021/jacs.5b05693. This Macro Scheduler (MJT Net Ltd, UK) script is a representative example of that used to automatically measure I(s) traces from 1,8-ODT-coated and blank (uncoated) Au substrates using an Agilent 5100 Scanning Tunnelling Microscope (interfacing with PicoView 1.14, Agilent Technologies). A short 'Guide to...' document is also included to introduce the user, as are additional files (Microsoft Excel spreadsheets and images) required by the script.